Residência multiprofissional em saúde da família: limites e possibilidades para mudança na formação profissional - Oliveira, Fernanda Rocco (2007)
This work analyzes a postgraduate formation experience of Multiprofissional Residency in Family Health. The text, initially, introduces the reader on Public Politics of Formation in Health of the Education and Health department, pointing actions and programs developed currently. In this movement, it focuses in the strategy of the RMSF developed by Casa de Saúde Santa Marcelina and Faculdade Santa Marcelina , in which the researcher was preceptor, between 2005 to 2007. From documentary and bibliographical revision of the RMSF, 14 interviews with fellow participants of the process of construction of this Residency had been carried through: preceptors, residents and coordinators. The analysis of the interviews was organized by means of thematic categories, based on the reading of the same ones. The conclusion taken from the existence of potentialities and limitations in the formation promoted by the Residency, as much in the technical scientific improvement as in the creativity stimulation and the commitment of the residents in face of the complex and multifaceted character of the professional work and the concrete problems of health of the population. Potentialities given for the narrower contact with the services of health and the sanitary conditions and social realities; and derived limitations, mainly, of traditions and conceptions of formation centered in the transmission of theoretical knowledge and technician, in a distant and out of context way of the practical and the politics of health of the SUS